2015
DOI: 10.1097/qco.0000000000000172
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhea in solid organ transplant recipients

Abstract: New epidemiologic data and new testing techniques offer an opportunity for research into better testing strategies for transplant patients with diarrhea. These newer testing strategies may offer better insight into the cause of diarrhea and more appropriate treatment for this illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 78 publications
(101 reference statements)
1
33
0
2
Order By: Relevance
“…The most common infectious causes of diarrhea following transplant include Norovirus, Clostridioides difficile, and Cytomegalovirus . Norovirus is a common cause of acute gastroenteritis in adults and is self‐limiting in immunocompetent hosts .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common infectious causes of diarrhea following transplant include Norovirus, Clostridioides difficile, and Cytomegalovirus . Norovirus is a common cause of acute gastroenteritis in adults and is self‐limiting in immunocompetent hosts .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified Norovirus and Clostridioides difficile infections (CDI) as important causes of post‐transplant infection that may have adverse effects on KTR graft function and mortality . However, there is limited information on the causative factors and complications of diarrheal infections in KTRs .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the prevalence of severe diarrhoea requiring hospitalization was 4.9% in total kidney transplant recipients. Previous studies have shown that diarrhoea in kidney transplant recipients is associated with a higher risk of graft dysfunction and all‐cause mortality . The present study supported those results, and additionally conducted stratified analyses by aetiology and immunosuppressant regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhea is a common complication in solid organ transplant recipients with an estimated prevalence of 20–50% . It can become a chronic and debilitating problem in transplant recipients due to their impaired ability to combat infections .…”
Section: Introductionmentioning
confidence: 99%